2017
DOI: 10.1128/mbio.01482-17
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Extremely Elongated, and Endocellular Bacterial Symbiont Supports Cuticle Formation of a Grain Pest Beetle

Abstract: The saw-toothed grain beetle, Oryzaephilus surinamensis (Silvanidae), is a cosmopolitan stored-product pest. Early studies on O. surinamensis in the 1930s described the presence of peculiar bacteriomes harboring endosymbiotic bacteria in the abdomen. Since then, however, the microbiological nature of the symbiont has been elusive. Here we investigated the endosymbiotic system of O. surinamensis in detail. In the abdomen of adults, pupae, and larvae, four oval bacteriomes were consistently identified, whose cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 84 publications
3
53
0
Order By: Relevance
“…The sawtoothed grain beetle O. surinamensis engages in an ancient symbiosis with cuticle supplementing Bacteroidetes bacteria [ 43 , 44 ]. Symbiotic beetles exhibited a context-dependent higher desiccation tolerance, especially a lower mortality during larval development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sawtoothed grain beetle O. surinamensis engages in an ancient symbiosis with cuticle supplementing Bacteroidetes bacteria [ 43 , 44 ]. Symbiotic beetles exhibited a context-dependent higher desiccation tolerance, especially a lower mortality during larval development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed an important symbiont contribution to larval survival, most likely through supported cuticle synthesis. However, the need for such support is probably highest for O. surinamensis , but holometabolous insects in general, during metamorphosis, when the entire insect body is reshaped, and as young adults, when the initially soft and weak cuticle is strengthened via sclerotization and melanization [ 22 , 43 , 49 ]. This would correlate with a control, at least partial, of the symbiont contribution via symbiont titer, but also means that the highest investment of the host is required during metamorphosis, when nutrients must be also invested into the reshaping of its own body, and no novel nutrients can be acquired until imagines hatch and are fully hardened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The building of a strong cuticle, a characteristic feature of coleopterans, requires a huge amount of tyrosine and phenylalanine amino acids, which are the precursors of the 3,4-dihydroxyphénylalanine (DOPA) amino acid involved in the cuticle melanization and sclerotization (see below). Endosymbiont contribution to host cuticle synthesis through aromatic amino acid supply appears to be a convergent strategy among beetles [ 52 54 ].…”
Section: Main Textmentioning
confidence: 99%
“…Besides weevils, early histological studies described the presence of bacteriome-associated endosymbiotic bacteria in horned powderpost beetles and grain borers (Bostrichidae) (Mansour, 1934;Buchner, 1954;Huger, 1956), saw-toothed grain beetles (Silvanidae) (Koch, 1931(Koch, , 1936Huger, 1956), soft-winged flower beetles (Dasytidae) (Stammer, 1933), false click beetles (Throscidae) (Stammer, 1933), and tree sap beetles (Nosodendridae) (Stammer, 1933). For decades, the microbiological nature of these endosymbiotic bacteria associated with the tiny minor beetles has been elusive, but recent molecular phylogenetic and genomic studies identified the bostrichid endosymbionts as belonging to the Bacteroidetes (Okude et al, 2017;Engl et al, 2018), the silvanid endosymbionts as allied to the bostrichid endosymbionts in the Bacteroidetes (Hirota et al, 2017;Engl et al, 2018), and the dasytid endosymbionts belonging to the γ-Proteobacteria (Weiss and Kaltenpoth, 2016). Meanwhile, the throscid endosymbionts and the nosodendrid endosymbionts are still to be characterized.…”
Section: Introductionmentioning
confidence: 99%